ANALISIS YURIDIS KEPATUHAN REGULASI PERLINDUNGAN DATA PRIBADI DALAM SOLUSI INTERNET OF THINGS (IOT) - Eka Ari Endrawati (Cahaya Ilmu Bangsa, 2024)
Indonesia is a country of law, a country that guarantees all citizens have equal rights in law and government. Advances in information technology are considered to be a force that can determine a person's fate. Cyber crime is a crime or illegal activity carried out through electronic world networks. Crime on the internet network is increasingly dangerous because the scope of this action is very broad. This research intends to conduct an in-depth analysis of the level of personal data protection law compliance in the context of IoT solutions. The normative legal research method uses a library search technique, which involves searching for journal materials or articles related to the title and theme that the author is studying. From the results of document analysis, it was identified that most companies and IoT solution developers have tried to implement compliance measures with personal data protection regulations, especially those regulated by the Personal Data Protection Law in Indonesia. The research results also show that there are still several obstacles in implementing compliance. The complexity of IoT technology, device diversity, and lack of deep understanding of regulations are the main obstacles. Some companies face difficulties in aligning privacy policies with the rapidly changing and complex dynamics of IoT. It is concluded that this research provides deep insight into the level of compliance with personal data protection regulations in IoT solutions. It is necessary to ensure the security and privacy of personal data in this ever-evolving system. By implementing the proposed recommendations, it is hoped that IoT solutions can more effectively meet regulatory compliance standards